Using The List of Minimum Requirements to Analyze Students’ Errors In Their English Compositions - Anna Stasya Prima Sari; Jontra Jusat Pangaribuan (Budapest International Research and Critics University, 2018)
This research was conducted to analyze the errors made by the students in their English compositions. The researchers used the list of Minimum Requirements which was developed by Fountain to analyze the students’ writing errors. Based on the data analysis, it was found that the students made 60 errors altogether in their English compositions entitled About Me. There are nine kinds of error made by the students. The students made 19 errors in punctuation (31.7%), 11 errors in preposition (18.3%), seven errors in concord/agreement (11.7%), seven errors in finite verbs (11.7%), six errors in articles (10%), four errors in spelling (6.7%), two errors in tenses (3.3%), two errors in verb groups (3.3%) and two errors in word choice (3.3%). It is advisable that the list of Minimum Requirements is used as a guideline to help the learners minimize their errors in writing.